Development of microprocessor learning media using zilog z-80 for vocational school students of electronic engineering expert program - Fathia, Nurul Fitri; Hanafi, Ivan; Rif'an, Muhammad (Jurnal Pendidikan Vokasi, 2018)
This development research aims to develop microprocessor learning media using Zilog Z80. The Learning Media quality is based on the following aspects: (1) media feasibility according to subject matter experts and media experts; (2) effective based on students ability test by pre test and post-test. The developed cycles and procedures refer to the ADDIE model (analysis, design, development, implementation, and evaluation). This development research produces learning media as microprocessor kits training and e-Learning namely "µProsessor" as learning support. Data analysis techniques to test the effectiveness of learning media using Paired Samples T-Test and Using a Likert scale to test the feasibility of learning media. The research results show that the feasibility of learning media is enough with a high score of above 88% and Paired Samples Test results for media effectiveness show an increase in the value of significant microprocessor capabilities. Measuring the improvement of the ability of students' microprocessors using N-gain (normalized gain). The results of the calculation of N-gain in the large group is 0.72 in the high category. Interpretation of the results of the research can be concluded that effective learning media as a learning media for microprocessors.